Dari Akuntabilitas Menuju Maslahah: Pengaruh Inventarisasi, Pemanfaatan, dan Pengamanan terhadap Optimalisasi Aset Tetap dalam Konteks Ekonomi Islam - Indriyani Pasaribu; Nurwani; Tri Inda Fadhila (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
This study investigates the impact of asset inventory, asset utilization, and asset safeguarding on the optimization of fixed assets—specifically land and buildings—within the Government of North Labuhanbatu Regency, through the lens of Islamic economics. Regional fixed assets constitute a component of public wealth that necessitates management that is accountable, efficient, and purpose-driven. Adopting a quantitative research design, this study employed a survey method involving 60 respondents, all of whom are asset managers within the Regional Financial and Asset Management Agency. Data were analyzed using multiple linear regression via SPSS Statistics (version 2025). The results reveal that both asset inventory and asset safeguarding exert a positive and statistically significant influence on fixed asset optimization. In contrast, asset utilization demonstrates a negative yet significant effect, suggesting that inappropriate or misaligned use may impede the optimization process. Collectively, the three variables exert a significant joint influence on fixed asset optimization. From an Islamic economic perspective, the stewardship of public assets constitutes an amanah (trust) that must be administered with fairness, efficiency, and a focus on public benefit (maslahah). Consequently, the implementation of a disciplined, integrated, and Sharia-compliant asset management framework is imperative to underpin sustainable public service delivery and regional development